Utilization of Natural resources to Improve Community Economy in Pangkep Regency: A Case Study of PT Semen Tonasa - Andi Nonong Sunrawali; Andi Sartika Juniarmita; Andi Tenri Lawa Putri Lanrang Haris; Muhammad Taufan Gunawan; Andi Dorawati Ishak (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the contribution of natural resource utilization by PT Semen Tonasa in improving the community economy in Pangkep Regency. The research focuses on direct and indirect economic contributions, the effectiveness of corporate social responsibility (CSR) programs, as well as the social and environmental impacts perceived by the community. A mixed methods approach with a case study design was employed. A survey was conducted with 100 respondents using a Likert-scale questionnaire, and in-depth interviews were conducted with 15 key informants (local government, community leaders, MSMEs, and company management). The results show that natural resource utilization by PT Semen Tonasa has a significant positive contribution to increasing community income (β = 0.412; p < 0.01), expanding job opportunities, and developing local MSMEs. CSR programs also significantly influence the improvement of local business capacity (β = 0.368; p < 0.05). However, some communities reported environmental impacts such as air pollution and health issues. Qualitative analysis confirms that although the community benefits economically, there is a strong demand for improved environmental governance. In conclusion, PT Semen Tonasa has significantly contributed to the local economy, but more inclusive sustainability strategies are needed to mitigate environmental impacts and enhance long-term community welfare.